1986
DOI: 10.1002/cyto.990070110
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis of membrane permeability properties influencing intracellular accumulation and efflux of fluorescein

Abstract: A flow cytometric investigation has been made on the membrane permeability properties that mediate intracellular turnover of fluorogenic substrates. The accumulation and efflux of fluorescein, consequent to the enzymatic turnover of fluorescein diacetate, were assessed in the presence of metabolic inhibitors and after treatment with membrane-active compounds.The metabolic poisons KCN and rotenone greatly inhibited only the fluorescein efflux, reducing the rate constant to as little as onetenth in relation to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 14 publications
3
25
0
Order By: Relevance
“…The cells were double stained using the following procedures: For green fluorescence, 2 . 10' cells/ml were suspended in phosphate-buffered saline (PBS) containing 136 mM NaC1, I 0 mM KH,P04, pH 7.2, and were incubated 1-2 min in the presence of 6 pM carboxyfluorescein-diacetate (Sigma C-8166; from a 1.2 mM stock solution in dimethylsulfoxide) at 37°C (28,29). The CF loading was kept low at about 0.1 fmoV cell, which was determined by using a spectrofluorimeter calibrated for CF.…”
Section: Fluorescent Staining Of Cellsmentioning
confidence: 99%
“…The cells were double stained using the following procedures: For green fluorescence, 2 . 10' cells/ml were suspended in phosphate-buffered saline (PBS) containing 136 mM NaC1, I 0 mM KH,P04, pH 7.2, and were incubated 1-2 min in the presence of 6 pM carboxyfluorescein-diacetate (Sigma C-8166; from a 1.2 mM stock solution in dimethylsulfoxide) at 37°C (28,29). The CF loading was kept low at about 0.1 fmoV cell, which was determined by using a spectrofluorimeter calibrated for CF.…”
Section: Fluorescent Staining Of Cellsmentioning
confidence: 99%
“…Studies with detergents and solvents indicated that the twin probes could be used to ' However, a practical limitation on the use of fluorescein in the present context is imposed by its relatively rapid efflux from a variety of cells with apparently intact cell membranes (6,8,19,22,23). An improved twocolour flow cytometric assay for membrane permeability is described here using a different pair of complementary fluorescent probe molecules.…”
mentioning
confidence: 99%
“…The efflux of fluorescein from living cells has been shown to be dependent on membrane integrity and 1 on the metabolic energy supply; indeed, the dye release is affected both by membrane-active agents and mitochondrial poisons (Sengbush et al, 1976;Baisch, 1978;Prosperi et al, 1986). Therefore, the monitoring of the kinetics of fluorescence decrease from anthracycline-treated cells may provide information on alterations induced by the drugs, either on membrane structures or energetic cell metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, when fluorescein diacetate (FDA) is used as the fluorogenic substrate, the efflux of the fluorescent product (fluorescein) has been shown to be influenced by membrane integrity (Rotman & Papermaster, 1966), inhibited by mitochondrial poisons and modulated by the presence or absence of glucose in the extracellular medium (Prosperi et al, 1986).). Therefore, the monitoring of the kinetics of fluorescence decrease in fluoresceinloaded cells may provide useful information on membrane functions, especially on permeability properties dependent on the metabolic energy supply.…”
mentioning
confidence: 99%